2019
DOI: 10.1096/fj.201900215rr
|View full text |Cite
|
Sign up to set email alerts
|

TG101348, a selective JAK2 antagonist, ameliorates hepatic fibrogenesis in vivo

Abstract: Hepatic fibrosis, characterized by an excessive extracellular matrix (ECM) accumulation, leading to scar‐tissue formation is a growing health problem worldwide. Hepatocellular damage due to liver injury triggers inflammation and transdifferentiation of quiescent hepatic stellate cells (HSCs) into proliferative, contractile, and ECM‐producing myofibroblasts. Involvement of the Janus kinase (JAK)‐2 pathway in the pathogenesis of fibrosis has been reported earlier. However, in this study, we have investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…Fed regulates the secretion of these cytokines, thus transforming the vicious circle to a virtuous one and preventing the epithelial cells from further injury. Our findings are in line with a previous study that Fed inhibits LPS-induced inflammatory cytokine IL-6, IL-1β and TNF-α secretion in macrophages [ 33 ], together suggesting the anti-inflammation effect of Fed.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Fed regulates the secretion of these cytokines, thus transforming the vicious circle to a virtuous one and preventing the epithelial cells from further injury. Our findings are in line with a previous study that Fed inhibits LPS-induced inflammatory cytokine IL-6, IL-1β and TNF-α secretion in macrophages [ 33 ], together suggesting the anti-inflammation effect of Fed.…”
Section: Discussionsupporting
confidence: 93%
“…These cytokines then activate fibroblasts to become myofibroblasts that in turn secrete collagen and other ECM proteins that stiffen the lung. Blocking JAK2/STAT3 signaling has been demonstrated to reduce both inflammation and fibrosis in murine model [ 12 , 33 ]. Here, we found that Fed reduced bleomycin-induced inflammatory response, decreased infiltration of immune cells and downregulated the secretion of profibrotic cytokines such as TGF-β1, TNF-α, IL-1β and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…Since IRF5 mediates hepatocyte death and liver fibrosis in mice as well as humans, modulation of IRF5 function may be another attractive approach to treat fibrosis. Finally, involvement of the Janus Kinase (JAK)-2 pathway in the pathogenesis of hepatic fibrosis, steatosis, ischemia-perfusion injury and HCC has been observed [ 93 ]. In the liver, the JAK2 pathway plays a critical role in regulation of multiple processes including cell growth, differentiation, proliferation and immune functions by activating growth hormones and cytokines including IFN-γ, IL-4, IL-6, IL-12, IL-13 and leptin [ 94 ].…”
Section: Role Of Liver-resident Macrophages In Hepatic Fibrosismentioning
confidence: 99%
“…In the liver, the JAK2 pathway plays a critical role in regulation of multiple processes including cell growth, differentiation, proliferation and immune functions by activating growth hormones and cytokines including IFN-γ, IL-4, IL-6, IL-12, IL-13 and leptin [ 94 ]. Selective JAK2 antagonist TG1011348 inhibits macrophage infiltration, expression of inflammatory markers and nitric oxide release from macrophages and attenuated HSC activation and collagen accumulation, suggesting its use as a potential therapy [ 93 ].…”
Section: Role Of Liver-resident Macrophages In Hepatic Fibrosismentioning
confidence: 99%
“…However, excessive and prolonged deposition of these proteins due to an uncontrolled wound healing response leads to fibrosis and fibrotic scar formation that affects the functional restoration of the tissue [ 1 , 2 ]. Apart from fibrosis in injured tissue, fibrosis is common in many pathological conditions, occurring in organs such as the liver [ 3 , 4 , 5 , 6 , 7 ], heart [ 8 , 9 , 10 , 11 , 12 ], kidneys [ 13 , 14 , 15 , 16 , 17 ], lungs [ 18 , 19 , 20 , 21 ], and systemic sclerosis [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%